Adjuvant nivolumab therapy may not improve disease‐free survival in resected acral lentiginous melanoma patients: A retrospective case series. Issue 11 (19th September 2022) - Maeda, Takuya; Yanagi, Teruki; Miyamoto, Kodai; Tokuchi, Keiko; Kitamura, Shinya; Ujiie, Hideyuki
Abstract: Adjuvant nivolumab therapy has been reported to improve the survival of melanoma patients. Acral lentiginous melanoma (ALM) has been reported to be less likely to respond to immune checkpoint inhibitors (ICIs) than other subtypes. However, the efficacy of adjuvant nivolumab therapy for ALM patients remains uncertain due to the low number of cases. In this single‐center retrospective case series, we analyzed the clinical data of patients with resected stage III/IV ALM who were referred to our department between April 1, 2004 and March 31, 2022. The analyzed clinical data included age, sex, TNM stage, treatments, adverse events and disease‐free survival (DFS). Enrolled patients were divided into a nivolumab group and a non‐ICI group according to the adjuvant therapy they received. In total, 27 patients were included. The nivolumab and non‐ICI groups had 5 and 22 patients, respectively. There were no significant differences in patient characteristics between the two groups. There were no serious treatment‐related adverse events in the non‐ICI group, but one patient in the nivolumab group developed type 1 diabetes. In the survival analysis, the DFS for the nivolumab group did not exceed that of the non‐ICI group in postoperative adjuvant therapy for ALM patients. Given that adjuvant nivolumab therapy sometimes results in serious adverse effects, the administration of the therapy may need to be carefully considered, especially for ALM patients.